Intestinal Failure and Short Bowel Syndrome in Crohn’s Disease: A Systematic Review - Boemer, Hayslan Theobaldo (2021)
Crohn's disease (CD) is an inflammatory, chronic and progressive disease that affects the digestive tract. Despite optimized drug therapy, the risk of multiple surgical interventions over the years is high, leading the patient to develop short bowel syndrome (SBS). Thus, adequate management in the postoperative period directly interferes with the long-term prognosis. Initially, most of these patients, due to hydro electrolytic disorders and absorptive incapacity inherent in SBS, will need parenteral nutritional support. According to the patient's residual digestive profile and according to nutritional management (oral, enteral, and/or parenteral), the intestine will evolve in its adaptive capacity. During this period, control agents are used for motility and intestinal secretion and, if necessary, GLP-2 agonists (intestinotrophic). In cases refractory to these treatments, we can still indicate surgical procedures to control motility, increasing intestinal length, and, finally, transplantation. CD is recurrent, and patients with SBS need a multidisciplinary approach with continuous monitoring to provide better intestinal rehabilitation and consequent quality of life.